Mobile Application Protection System: A Secured Architecture (International Journal of Engineering and Computer Science, 2014)
Mobile application market is gaining a lot of attention with the introduction of increase in speed, accessibility and capacity to download huge amount of software applications from internet to the mobile devices. Mobile application protection is a critical issue for mobile network operators, content providers and all players who involved in the mobile software business chain. This paper proposes an architecture where trusted mobile software environment is designed to control the execution of mobile application. A software ID which is dynamically updated and shared key are created and used for authorization of mobile application execution requests. This solution can prevent many mobile application crack issues which include copy of the mobile application to unauthorized mobile devices and modification of mobile application.